TRANSFORMATION OF HUMAN RESOURCE MANAGEMENT IN THE ERA OF REGIONAL DECENTRALIZATION AND DIGITAL REVOLUTION - Bahri, M. Irvanni; Tambunan, Ayu Anggraini; Zulfikar (Jurnal Manajemen Rekayasa dan Inovasi Bisnis, 2025)
Local governments are shifting their views on human resource management (HRM) due to regional decentralization, which aims to strengthen the relationship between citizens and local governments through discussion forums. This change in perspective has implications for how local governments should integrate HRM into other operational tasks. A systematic review of the literature was conducted to understand change management and HRM in the context of regional decentralization and the impact of the digital revolution on organizations. The study screened 28,452 journals in the Web of Science (WoS) and 18 journals in Scopus, resulting in 306 journals. The study found significant differences between WoS and Scopus databases, with WoS having more journals despite using the same keywords and many discussing topics outside the context of title and keywords. The results conclude that the digital revolution impacts all organizations, both commercial and governmental, and that organizations must survive in the industrial age by laying a solid foundation through effective people management. Change requires embracing new cultures and being curious and creative to function effectively in an open-change environment.